2018
DOI: 10.21037/jgo.2017.10.10
|View full text |Cite
|
Sign up to set email alerts
|

Management of locally advanced rectal cancer in the elderly: a critical review and algorithm

Abstract: Colorectal cancer incidence and death rates have been declining over the past 10 years. However, it remains the second leading cause of death in men ages 60-79 and the third leading cause of death in men over 80 and in women over 60 years old. However, there is little data specific to the treatment of the elder patient, since few of these patients are included in trials. With the advent of improved therapies, there are many alternative options available. Still, no definitive consensus or guidelines have been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 130 publications
0
13
0
Order By: Relevance
“…Recent advances in treatments directed at lower rectal carcinoma (LRC) have resulted in multimodal therapies with curative potential and the preservation of quality of life. Pre-operative chemoradiotherapies (pCRT) followed by radical surgery are attracting increasing attention worldwide1-3. Previous studies reported that radical surgery after pCRT for LRC contributed to anal preservation, reduced the rate of local recurrence, and secured a circumferential resection margin4-7.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in treatments directed at lower rectal carcinoma (LRC) have resulted in multimodal therapies with curative potential and the preservation of quality of life. Pre-operative chemoradiotherapies (pCRT) followed by radical surgery are attracting increasing attention worldwide1-3. Previous studies reported that radical surgery after pCRT for LRC contributed to anal preservation, reduced the rate of local recurrence, and secured a circumferential resection margin4-7.…”
Section: Introductionmentioning
confidence: 99%
“…This may lead to biased results [22,23,46]. The aging population, the rising incidence and the improved prognosis of rectal cancer will increase the need for surgery in the elderly population in the future [4,26]. Successful treatment of elderly patients depends on whether it is done safely, allowing them to preserve good quality of life, and a life-expectancy that is not reduced by the treatment [2].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are few ideal markers available for the clinician to choose the optimal treatment (e.g., neoadjuvant RT or not) at the time of diagnosis for RC. Furthermore, the prognosis of RC patients varies significantly, even for those with the same TNM stage [ 10 ]. Therefore, biomarkers for better risk evaluation might be essential to assess the tumor status, identify patients with a high risk of progression and help clinicians make the best therapeutic plan at the time of diagnosis in RC.…”
Section: Introductionmentioning
confidence: 99%